Factors associated with rural Mexican American gang activity - Acosta, Sylvia J., author; Rosén, Lee A., advisor (Colorado State University. Libraries, 2008)
This study examines factors related to Mexican American gang involvement in rural communities. Data for this study were obtained from a larger, cross sectional study on adolescent drug use in rural areas. Survey data from a total of 746 males (373 gang members and 373 non-gang members) and 290 females (145 gang members and 145 non-gang members) were analyzed regarding factors of parental caring and family caring, parental permissiveness, religiosity, mental health factors, and alcohol and marijuana use. It was hypothesized that low levels of parental caring and low levels of religiosity would be associated with gang membership. Mental health factors such as low self-esteem and high anger and depression were also expected to be risk factors for gang membership. Logistic regression was used to identify key risk factors related to joining a gang for Mexican American males and females. For males, alcohol and marijuana use, having caring parents and family, parental permissiveness, and anger were significantly related to gang involvement in the analysis. For females, the same variables with the addition of age were significantly related to gang involvement. Religiosity, self-esteem, and depression were not associated with gang involvement in this study. Implications for gang prevention and intervention planning for rural communities are discussed.
Keywords: family; gang; gender differences; Hispanic; Hispanic/Latino; Latino; Mexican-American; rural communities; youth gang; social psychology; individual and family studies; Hispanic American studies